2012
DOI: 10.1016/j.ecss.2012.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual variations of macrobenthic communities over three decades in a land-locked coastal lagoon (Santo André, SW Portugal)

Abstract: Keywords: macrobenthic communities land-locked coastal lagoon ecological status long-term changes water framework directive a b s t r a c t Santo André is an enclosed brackish water coastal lagoon with temporary connections to the sea by a man-made channel. The exchange and mixture of saltwater and freshwater is irregular and the lagoon may show daily and seasonal fluctuations, but also long-term variation. Different benthic communities may be present along the annual cycle according to the magnitude of episod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…The benthic macrofauna density in both lagoons was higher than in Albufeira coastal lagoon (Quintino and Gentil, 1988) and approximately 50% higher than the ones observed in Santo André, where mean annual densities were always lower than 10x10 3 ind.m -2 (Correia et al, 2012).…”
Section: Benthic Macrofauna Structurementioning
confidence: 65%
“…The benthic macrofauna density in both lagoons was higher than in Albufeira coastal lagoon (Quintino and Gentil, 1988) and approximately 50% higher than the ones observed in Santo André, where mean annual densities were always lower than 10x10 3 ind.m -2 (Correia et al, 2012).…”
Section: Benthic Macrofauna Structurementioning
confidence: 65%
“…The present results showed that, like in open brackish systems, such as estuaries (Silva et al, 2012), the structure of benthic communities is strongly associated and dependent of freshwater inputs. Thus, and although additional information is required to quantify this relationship, it is reasonable to consider that unsustainable groundwater abstraction can have a strong impact on the biological communities of enclosed lagoons.…”
Section: Discussionmentioning
confidence: 87%
“…Santo André lagoon, on the other hand, appears to buffer freshwater input and displays a certain degree of zonation (e.g. Elliott & Whitfield, 2011;Correia et al, 2012;Félix et al, 2013a, b).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations